2015
DOI: 10.1111/bij.12692
|View full text |Cite
|
Sign up to set email alerts
|

Recent and rapid diversification of the small carpenter bees in eastern North America

Abstract: Bees fulfil a critical ecological role as pollinators, significantly contributing to the reproductive success of myriad angiosperm species. Although increasingly appreciated for their agricultural contributions, relatively little is yet known about the natural history of the vast majority of the more than 20 000 wild bee species worldwide. The small carpenter bee genus Ceratina occurs globally, and is represented in North America by its most recently diverged subgenera, Ceratinula and Zadontomerus. Recent gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…We note that the mitochondrial mutation rate for Caenorhabditis elegans (Maupas) is estimated as 9.7 × 10 -8 mutations per site per generation, close to the rate for D. melanogaster, and that they have mitochondrial AT biases of 76% and 82% respectively. Previous studies have reported an AT bias of 74% for the same barcoding region as in our study (Groom et al 2014a;Shell and Rehan 2016), and our Ceratina haplotypes had an AT bias of 78%. The number of generations was determined as two per year based on nest contents data from the Victorian and South Australian sites (Dew and Rehan, unpublished data), which also corresponds to detailed studies on the Queensland population (Rehan et al 2010b(Rehan et al , 2011(Rehan et al , 2014.…”
Section: Historical Demographysupporting
confidence: 75%
See 3 more Smart Citations
“…We note that the mitochondrial mutation rate for Caenorhabditis elegans (Maupas) is estimated as 9.7 × 10 -8 mutations per site per generation, close to the rate for D. melanogaster, and that they have mitochondrial AT biases of 76% and 82% respectively. Previous studies have reported an AT bias of 74% for the same barcoding region as in our study (Groom et al 2014a;Shell and Rehan 2016), and our Ceratina haplotypes had an AT bias of 78%. The number of generations was determined as two per year based on nest contents data from the Victorian and South Australian sites (Dew and Rehan, unpublished data), which also corresponds to detailed studies on the Queensland population (Rehan et al 2010b(Rehan et al , 2011(Rehan et al , 2014.…”
Section: Historical Demographysupporting
confidence: 75%
“…6.2 x 10 -8 mutations per site per generation as an estimate of the mutation rate for Ceratina australensis (Haag-Liautard et al 2008). This method follows a previous study on demographic history in Fijian halictine bees in the genus Lasioglossum (Groom et al 2014a) and North American Ceratina species (Shell and Rehan 2016). We note that the mitochondrial mutation rate for Caenorhabditis elegans (Maupas) is estimated as 9.7 × 10 -8 mutations per site per generation, close to the rate for D. melanogaster, and that they have mitochondrial AT biases of 76% and 82% respectively.…”
Section: Historical Demographymentioning
confidence: 99%
See 2 more Smart Citations
“…This species ranges from Georgia north to Ontario and east to Nova Scotia (Rehan and Sheffield 2011;Shell and Rehan 2015). Unlike many temperate insects (Danks 1991;Denlinger 2002), C. calcarata overwinters as an adult (Rehan and Richards 2010a).…”
Section: Introductionmentioning
confidence: 99%